Bilingual ‘Tagging’ of Financial Accounts in Demotic and Greek - Mairs, Rachel (Zeitschrift für ägyptische Sprache und Altertumskunde, 2012)
‘Bilingual’ documents, with text in both Demotic and Greek, can be of several sorts, ranging from complete translations of the same information (e.g. Ptolemaic decrees) to those where the information presented in the two languages is complementary (e.g. mummy labels). The texts discussed in this paper consist of a number of examples of financial records where a full account in one language (L1) is annotated with brief pieces of information in a second language (L2). These L2 ‘tags’ are designed to facilitate extraction of summary data at another level of the administration, functioning in a different language, and probably also to make the document accessible to those who are not literate in the L1.